PENINGKATAN PERAN KADER POSYANDU DALAM PERCEPATAN PENURUNAN STUNTING MELALUI EDUKASI PEMBERIAN ZAT GIZI MIKRO - Indah Fitri Andini; Lydia Febrina; Yeni Puspita; Farida Esmianti; Ayu Pravita Sari (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Accelerating stunting reduction is the government's focus in the health sector. The micronutrients given to pregnant women are in the form of blood supplement tablets containing iron and folic acid. Meanwhile, nutrition for toddlers is in the form of two vitamin A capsules according to the dosage and giving Zinc tablets and ORS according to the management for toddlers suffering from diarrhea. The efforts made to recognize, prevent and overcome nutritional problems include regularly weighing, giving breast milk to babies from birth to 6 months of age, varying food menus, using iodized salt, and providing nutritional supplements as recommended by health workers. Increasing the knowledge and skills of cadres through training was a method of implementing this community service activity. The method for developing this activity was by providing training and refreshing for posyandu cadres and village midwives as well as assisting cadres during the implementation of the activity. Monitoring and evaluation was carried out by the implementation team for cadres. This activity achieved results, namely the formation of a stunting care cadre group, the availability of facilities and infrastructure to support activities such as modules, tools and materials to increase cadres' knowledge and skills. After the training, there was an increase in cadres' knowledge and skills regarding Micronutrients needed by pregnant women and toddlers.